2022
DOI: 10.1080/14786419.2022.2125965
|View full text |Cite
|
Sign up to set email alerts
|

Ginger and parsley essential oils: chemical composition, antimicrobial activity, and evaluation of their application in cheese preservation

Abstract: Chemical composition and in vitro antimicrobial activity of parsley [Petroselinum crispum (Mill.) Fuss] and ginger (Zingiber officinale Roscoe) essential oils from store-bought parsley plants and ginger rhizomes were evaluated. A sensory analysis was performed on aged cheese slices treated with a mix of each essential oil and seed oil. Parsley essential oil was selected as the best compromise between sensory influence and antimicrobial activity and tested to evaluate its antifungal effects on cheese slices exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…24 Hydrodistillatin is the main method to obtain the essential oil. 25,26 Because these compounds are insoluble in water, aqueous solvents are not suitable for their extraction. Whether obtained from the seeds or the herb, terpenes and terpenoids with low molecular weight comprise the major ingredients of parsley essential oil, followed by phenylpropanoids as the second group of major ingredients.…”
Section: ■ Indigenous Traditional Knowledgementioning
confidence: 99%
See 3 more Smart Citations
“…24 Hydrodistillatin is the main method to obtain the essential oil. 25,26 Because these compounds are insoluble in water, aqueous solvents are not suitable for their extraction. Whether obtained from the seeds or the herb, terpenes and terpenoids with low molecular weight comprise the major ingredients of parsley essential oil, followed by phenylpropanoids as the second group of major ingredients.…”
Section: ■ Indigenous Traditional Knowledgementioning
confidence: 99%
“…Aerial parts of the plant also contain a certain amount of essential oil from which some volatile compounds may be isolated; however, the yield of essential oil content of the seeds is about 10 times higher than that of the herb (1.2–1.7% in seeds vs 0.16% in aerial parts) . Hydrodistillatin is the main method to obtain the essential oil. , Because these compounds are insoluble in water, aqueous solvents are not suitable for their extraction. Whether obtained from the seeds or the herb, terpenes and terpenoids with low molecular weight comprise the major ingredients of parsley essential oil, followed by phenylpropanoids as the second group of major ingredients.…”
Section: Chemistry Of Parsleymentioning
confidence: 99%
See 2 more Smart Citations
“…The use of medical plants has been demonstrated to be useful in hematological malignancies, and this fact is undoubtedly arousing because every day clinicians in hematology and oncology units are confronted with the adverse effects of traditional drugs, which can sometimes cause the stop of the treatment if it is intolerable for patients and dangerous for their health [ 57 , 58 , 59 , 60 , 61 ]. Scientific research showed the efficacy of different natural compounds both in the prevention and cure of cancer [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Allegra and colleagues [ 33 ] studied the effects of rosemary in various types of cancer and put in evidence its action in augmenting antioxidant molecules, decreasing pro-inflammatory cytokines and preventing neo-vascularization, all functions crucial for the insurgence and progression of a tumor in general.…”
Section: Cinnamon and Hematological Malignanciesmentioning
confidence: 99%